Carbamazepine-Induced Hematological and Immunological Alterations in Egyptian Children with Idiopathic Generalized Seizures - El-Shimi, Ola Samir; Farag, Amina Ali; El-Rebigi, Amany Mohammed; Kharboush, Taghrid Gamaleldin; Bayomy, Hanaa El-Sayed; Khashaba, Rana Atef (Journal of Child Science, 2021)
Carbamazepine (CBZ) is one of the oldest antiepileptic drugs (AEDs) that is still used for the treatment of tonic-clonic seizures in children. Long-term use of AEDs induces potential toxic effects that may remain undetermined for a long time. Earlier studies have revealed a wide spectrum of hematological toxicities associated with CBZ. This study was conducted to unveil the toxic effects of carbamazepine as an antiepileptic monotherapy on hematological and immunological parameters in a group of Egyptian pediatric patients using it for different durations. Fifty pediatric epileptics of either sex were enrolled; 38 were taking CBZ as antiepileptic monotherapy for ≥ 6 months and 12 were newly diagnosed untreated patients. Hematological and immunological parameters studied were compared with their age and sex-matched 15 controls and among groups. CBZ was found more toxic for total leukocyte count, lymphocyte count, serum IgA and IgM levels (p < 0.001, 0.001, < 0.001, < 0.001, respectively). Hemoglobin level, platelets count, serum C4 level and IgA were negatively correlated with serum CBZ level (Spearman's rho = – 0.62, – 0.42, – 0.34, – 0.13; p < 0.001, 0.008, 0.04, 0.44, respectively). CBZ treatment duration associated inversely with platelets, lymphocyte, and eosinophil counts (p < 0.001, 0.03, 0.01, respectively). Epileptic children on CBZ monotherapy had their hematologic and immunologic systems affected, which mandates routine monitoring of these children.
Keywords: carbamazepine; immunological effects; hematological effects; children; Egypt